2018
DOI: 10.1002/hfm.20733
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of smartwatch usage and its usability

Abstract: This study aims to explore usability issues of watch‐type wearable devices and to suggest guidelines for improved operation of smartwatches. To do so, we conducted a series of surveys, interviews, and task performance experiments. Thirty smartwatch users from ages 20 to 43 years were recruited. Users’ experiences of smartwatches were collected via a weeklong, online‐based diary study, which consisted of various tasks to be completed while smartwatches were in use. Our study assessed usability problems associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…In the domain of smartwatches, initial efforts arose in the last couple of years. Chun et al [11] conducted a qualitative study to access the usage and usability of smartwatches and elaborated guidelines for future smartwatches. Park et al [33] examined different types of menu interfaces for smartwatch applications in a qualitative study.…”
Section: Theoretical Foundation and Related Researchmentioning
confidence: 99%
“…In the domain of smartwatches, initial efforts arose in the last couple of years. Chun et al [11] conducted a qualitative study to access the usage and usability of smartwatches and elaborated guidelines for future smartwatches. Park et al [33] examined different types of menu interfaces for smartwatch applications in a qualitative study.…”
Section: Theoretical Foundation and Related Researchmentioning
confidence: 99%
“…Smartwatches present a challenging environment, possessing small screens and few buttons. Indeed, Chun et al (2018) found these devices suffer from several usability issues. Casano et al (2016) did develop 'Estimate It!…”
Section: Smartwatches and Behaviormentioning
confidence: 99%
“…There have been numerous efforts that aimed to address and alleviate the usability issues of smartwatch usage (e.g., [23,24,35,36]). Usability evaluations were conducted to assess the usability of smartwatches in an academic setting, where a cheating paradigm was used an example [36].…”
Section: Related Workmentioning
confidence: 99%
“…A design approach for wrist-worn wearables, which integrates micro-interaction and multi-dimensional graphical user interfaces, was proposed to offer guidelines to overcomes the challenges of the interaction paradigmatic shift [23]. The usability of smartwatch operations was qualitatively studied to identify issues that impact information display, control, learnability, interoperability, and subjective preference [24]. The findings highlighted several limitations of wearable devices, such as its poor display of visually rich content and its variable interoperability.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation